A large aneurysmal bone cyst of the clavicle in a 5-year-old child: a case report and review of literature. Issue 3 (May 2021) - Alrabayah, Mustafa; Alisi, Mohammed S.; Abdulelah, Ahmed A.; Atiyat, Bashir; Alnawaiseh, Hadeel
Abstract : Aneurysmal bone cyst of the clavicle is rarely reported in the literature. The average age of diagnosis in the reported cases is 12 years with female gender and medial third location predilection. We reported a case of a 5-year-old male child who presented with an incidental finding of right clavicular lesion on chest radiograph. Further evaluation revealed an aneurysmal bone cyst in the lateral end of the right clavicle. On the initial follow-up visit (after 6 months of observation), the lesion size increased to four-folds of the initial size. Complete subperiosteal resection was done with no recurrence noticed up to 4 months postoperatively. This study illustrates the importance of listing the aneurysmal bone cyst in the differential diagnosis of expansile clavicular lesions in young children.